Barriers in Pharmaceutical Services Focusing on Stunting and the Need for Digital Learning Media: A Qualitative Study of Community Pharmacists - Firdawati Amir Parumpu; Pratiwi Wikaningtyas; Satibi Satibi; Septi Muharni; Ananda Putri Purwanto; Kusnandar Anggadiredja (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: The strategic role of community pharmacists in pharmacy services focused on stunting in Indonesia is still limited, thus requiring resource support. The presence of digital learning media is expected to enhance competence. This study explores the barriers to implementing pharmacy services focused on stunting and the needs in developing digital learning media to improve the competence of community pharmacists. Methods: A descriptive-qualitative study with structured interviews covering two main research topics. Community pharmacists who are active in community facilities were recruited using purposive sampling techniques and have undergone interview consent. Results: The research findings are mapped into two main domains, namely the barriers to the implementation of stunting-focused pharmaceutical services and the need for digital learning media to enhance the competence of community pharmacists. Barriers are found in 1) internal factors, 2) external factors, and 3) system factors, it indicates an urgent need for digital learning media with 4) comprehensive materials related to stunting, 5) specific competence, 6) management guidelines, and 7) integration of digital technology in pharmaceutical services related to stunting, which are highly needed to improve the competence of community pharmacists in implementing stunting-focused pharmaceutical services in Indonesia. Conclusions: The finding of converging obstacles faced by community pharmacists in pharmaceutical services focusing on stunting and the enthusiasm for developing digital learning media to improve community pharmacists' competence becomes a strategic solution. There needs to be resource support for community pharmacists to play a role in pharmaceutical services focused on stunting in the future.